A review of plasma-assisted catalytic conversion of gaseous carbon dioxide and methane into value-added platform chemicals and fuels. Issue 48 (2nd August 2018) - Puliyalil, Harinarayanan; Lašič Jurković, Damjan; Dasireddy, Venkata D. B. C.; Likozar, Blaž
Abstract : The review focuses on the valorisation of two major greenhouse gases (methane and carbon dioxide) utilising different hybrid plasma reactors where valuable chemicals such as higher hydrocarbons, alcohols, aldehydes, carboxylic acids, etc. are produced. Abstract : CO2 and CH4 contribute to greenhouse gas emissions, while the production of industrial base chemicals from natural gas resources is emerging as well. Such conversion processes, however, are energy-intensive and introducing a renewable and sustainable electric activation seems optimal, at least for intermediate-scale modular operation. The review thus analyses such valorisation by plasma reactor technologies and heterogeneous catalysis application, largely into higher hydrocarbon molecules, that is ethane, ethylene, acetylene, propane, etc., and organic oxygenated compounds, i.e. methanol, formaldehyde, formic acid and dimethyl ether. Focus is given to reaction pathway mechanisms, related to the partial oxidation steps of CH4 with O2, H2 O and CO2, CO2 reduction with H2, CH4 or other paraffin species, and to a lesser extent, to mixtures' dry reforming to syngas. Dielectric barrier discharge, corona, spark and gliding arc sources are considered, combined with (noble) metal materials. Carbon (C), silica (SiO2 ) and alumina (Al2 O3 ) as well as various catalytic supports are examined as precious critical raw materials ( e.g. platinum, palladium and rhodium) or transition metal ( e.g. manganese, iron, cobalt, nickel and copper) substrates. These are applied for turnover, such as that pertinent to reformer, (reverse) water–gas shift (WGS or RWGS) and CH3 OH synthesis. Time-on-stream catalyst deactivation or reactivation is also overviewed from the viewpoint of individual transient moieties and their adsorption or desorption characteristics, as well as reactivity.